KAJIAN TEOLOGIS DAN PRAKTIS: PENERAPAN KEPEMIMPINAN TUHAN YESUS BAGI TERANG DUNIA BERDASARKAN FILIPI 2:5-8 - Pinondang Siregar; Hadi, Tan (EKKLESIA: Jurnal Teologi dan Pendidikan Kristiani, 2025)
Abstract: This study thoroughly examines the leadership model of Jesus Christ, which is rooted in the theological principles found in Philippians 2:5-8. The study then formulates practical guidelines for contemporary leadership based on these principles. Often referred to as the "Christ Hymn," these verses present a foundation of leadership based on kenosis (self-emptying) and radical humility. This foundation contrasts with worldly leadership models based on power and domination. Using a qualitative approach that incorporates biblical exegesis and comparative literature studies between theology and management theory, the study identifies three main pillars of Christ's leadership: willingness to relinquish privileges, absolute obedience, and self-sacrifice. The study's results show that adopting Christ's attitude transforms leadership from a position of authority into a ministry focused on the well-being and growth of those being led. Practical implications include developing an empathetic, collaborative, and highly ethical organizational culture that challenges leaders in churches and secular organizations to prioritize the common good over personal ambition. Abstrak: Penelitian ini mengkaji secara mendalam model kepemimpinan Tuhan Yesus Kristus yang berakar pada prinsip-prinsip teologis dalam Filipi 2:5-8, untuk merumuskan panduan praktis bagi kepemimpinan kontemporer. Ayat-ayat ini, sering disebut sebagai "Himne Kristus", menyajikan landasan kepemimpinan yang bertumpu pada kenosis (pengosongan diri) dan kerendahan hati radikal, yang kontras dengan model kepemimpinan duniawi yang berasaskan kekuasaan dan dominasi. Melalui pendekatan kualitatif dengan metode eksegesis biblikal dan studi literatur komparatif antara teologi dan teori manajemen, penelitian ini mengidentifikasi tiga pilar utama kepemimpinan Kristus: kerelaan melepaskan hak istimewa, ketaatan mutlak, dan pengorbanan diri. Hasil kajian menunjukkan bahwa penerapan sikap Kristus ini mentransformasi kepemimpinan dari sekadar posisi otoritas menjadi pelayanan yang berfokus pada kesejahteraan dan pertumbuhan orang yang dipimpin. Implikasi praktisnya mencakup pengembangan budaya organisasi yang empatik, kolaboratif, dan berintegritas tinggi, menantang para pemimpin di gereja dan organisasi sekuler untuk mengedepankan kepentingan bersama di atas ambisi pribadi.